Knowledge, attitudes, and practices of esophageal cancer patients regarding pulmonary rehabilitation training - Wang, Wei; Xing, Wenqun; Chen, Peinan; Sun, Haibo; Wang, Zongfei; Zheng, Yan; Yu, Yongkui; Zeng, Deming (Frontiers in Public Health, 2025)
IntroductionThis study aimed to assess the knowledge, attitudes, and practices (KAP) of esophageal cancer patients concerning pulmonary rehabilitation training.MethodsA cross-sectional study was conducted at the Henan Cancer Hospital from July 1, 2024, to August 31, 2024. Data were collected through questionnaires that gathered demographic information and KAP scores.ResultsA total of 530 esophageal cancer patients participated, including 197 (37.17%) regular smokers and 145 (27.36%) regular alcohol consumers. The mean ± SD scores were 7.78 ± 4.56 for knowledge (range: 0–20), 40.42 ± 4.66 for attitudes (range: 10–50), and 21.13 ± 3.08 for practices (range: 5–25). Correlation analyses showed positive relationships between knowledge and attitude scores (r = 0.335, p < 0.001), knowledge and practice scores (r = 0.323, p < 0.001), and attitude and practice scores (r = 0.567, p < 0.001). Structural Equation Modeling (SEM) indicated significant effects of knowledge on attitude (β = 0.420, p < 0.001) and attitude on practice (β = 0.711, p < 0.001).ConclusionEsophageal cancer patients showed inadequate knowledge but positive attitudes and proactive practices regarding pulmonary rehabilitation. These findings highlight the need for targeted educational interventions to improve patient knowledge, enhancing overall engagement in rehabilitation practices.